ANALISIS IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS PADA KEBIJAKAN PENDIDIKAN MULTIKULTURAL DI CABANG DINAS PENDIDIKAN WILAYAH IV JAWA BARAT - Hilman Akhmad Sadikin; Hinggil Permana; Chairil Fajar Hardiansyah; Rafif Zaki Rabbani; Ridho Anugerah Putera (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of the Sustainable Development Goals (SDGs) in multicultural education policies at the Regional Education Office Branch IV in West Java. This study employs a qualitative approach through field research, utilizing data collection techniques such as observation, interviews, and documentation. The data obtained were then analyzed using a descriptive analysis model consisting of data reduction, data presentation, and drawing conclusions. The results indicate that the West Java Regional Education Office IV has integrated the values of diversity, equity, and inclusivity through multicultural-based curriculum policies, teacher training programs, and social programs such as Poe Ibu (Sapoe Sarebu), which strengthen cross-cultural social solidarity. However, this study found several major challenges, such as uneven distribution of educational facilities, uneven teacher capacity, and a weak policy evaluation system. Overall, the implementation of multicultural education policies in the West Java Regional Education Office IV has proven to make a positive contribution to the achievement of SDG 4 and SDG 10,